(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Companies achieving sustainable business practices through Environmental Social and Governance (ESG) metrics integration now drive transparency and stakeholder involvement effectively. Electing qualitative research methods allows this investigation to study ESG metrics' effects on corporate sustainability strategy development through text analysis performed using both Latent Dirichlet Allocation (LDA) and Correspondence Analysis (CA) on ESG reports, regulatory texts, and academic publications. ESG metrics demonstrate essential importance in both corporate governance structures and regulatory conformity, as well as stakeholder commitment and financial planning applications. Future sustainability trends, together with corporate accountability, social impacts, and risk management, formed ten main themes that emerged from this analysis. The remaining themes were environmental practices with credibility, ESG reporting standardization, strategic ESG initiatives, and ESG disclosure communication and investor influence, followed by regulatory compliance and climate risk management and financial reporting with ESG risk analysis. The research objectives align well with the identified themes according to thematic mapping and CA results, which together create an extensive framework for ESG metric assessment in corporate sustainability strategies. A thorough analysis demonstrates that organizations must prioritize disclosure of ESG metrics together with sound governance systems while allowing investors to play a role and follow regulations in order to advance sustainability. Corporate decision-makers need to understand the essential implications that emerge from these findings because they demonstrate why structured ESG implementation methods are vital. Research must continue to analyze the developing ESG reporting environment and emerging regulatory changes and technological advancements that improve corporate accountability and governance transparency.